2005
DOI: 10.1086/431497
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Severe Rotavirus Diarrhea in New Delhi, India, and G and P Types of the Infecting Rotavirus Strains

Abstract: A total of 62,475 children <5 years old from a defined population of approximately 500,000 children and adults from slums in New Delhi, India, were assessed for 1 year by means of passive surveillance, to identify children who were hospitalized for diarrhea. The incidence of severe rotavirus diarrhea was estimated, and the G and P types of the infecting rotavirus strains were determined and were correlated with the clinical severity of diarrhea. Of 584 children who were hospitalized with diarrhea, 137 (23.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
64
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 28 publications
(21 reference statements)
22
64
3
Order By: Relevance
“…Thus children below 1 year of age are found to be more susceptible to rotavirus infection and it may be due to lack of fully developed immune system. The results of the present study are in agreement with other previous reports (Sarvanan et al, 2004;Bahl et al, 2005;Kang et al, 2009). …”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 94%
See 1 more Smart Citation
“…Thus children below 1 year of age are found to be more susceptible to rotavirus infection and it may be due to lack of fully developed immune system. The results of the present study are in agreement with other previous reports (Sarvanan et al, 2004;Bahl et al, 2005;Kang et al, 2009). …”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 94%
“…Thus, analysis of season in relation to rotavirus infection from Punjab revealed a significant association of the occurrence of infection with cooler months. The results of the present study are comparable with previous studies (Saravanan et al, 2004;Bahl et al, 2005;Kang et al, 2009;Kaur, 2011), who have reported the pre-dominance of human rotavirus infection during cooler months in India. The correlation of rotavirus gastroenteritis with the age of the subject is studied by grouping the children of different age into eight groups, as depicted in (Table 1).…”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 92%
“…The Indian Rotavirus Strain Surveillance Network carried out a multi-centric study in seven different regions of India and reported that rotavirus was detected in stools of 39% children aged <5 years [3]. Inclusion of children at hospitals caring for lower acuity diarrheal episodes or less severe disease may account for a lower percentage of rotavirus positive cases among the total number of enrolled patients in our study compared with previous studies [3,[8][9][10][11][12][13][14][15].…”
Section: Fig 2 Monthly Distribution Of Rotavirus-positive Patients mentioning
confidence: 65%
“…Other studies also reported an increased predominance of G9 and its association with severe diarrhea in Latin America 22 and in the United Kingdom where 71% of patients infected with G9P2A [6] required hospitalization and 33% of those who were admitted were severely dehydrated. 23 However, G9 association with increased severity is debatable as others reported that G1 had greater association with severe dehydration when compared with G9, 24,25 whereas other studies showed no difference of severity with any specific G-genotypes. [26][27][28] Differences in clinical severity associated G-genotypes may rely on the geographical origin of the strain or associated P-genotypes.…”
Section: Discussionmentioning
confidence: 98%